Augustus Saint-Gaudens papers - Saint-Gaudens, Augustus, 1848-1907.; Crosby, J. F.
Includes correspondence with Daniel H. Burnham concerning the Chicago World's Fair of 1893 and other matters; Saint-Gaudens's letters to Theodore F. Dwight and Charles Moore; and remarks on Saint-Gaudens by J. F. Crosby.
Sculptor and artist.
Collection material in English.
Crosby's remarks were previously cataloged separately as part of the Miscellaneous Manuscripts collection.
Keywords: Burnham, Daniel Hudson, -- 1846-1912 -- Correspondence; Dwight, Theodore F. -- Correspondence; Moore, Charles, -- 1855-1942 -- Correspondence; Exhibitions -- Illinois; Artists; Sculptors